ANALISIS E-MODUL KIMIA MADRSAH ALIYAH (MA) DALAM MENINGKATKAN PROSES PEMBELAJARAN DI BALAI PENDIDIKAN DAN KEAGAMAAN MEDAN - Intan Pulungan (Balai Diklat Keagamaan Medan, 2022)
This research was conducted using the classical method, meaning that the research process can be carried out with the condition that there are limited meetings around high schools or Madrasah Aliyah in the area of ​​​​the Center for Education and Religion (BDK) Medan. The Covid-19 pandemic, which has not been completed until now, has caused the learning process to not run well. Therefore, an analysis of teaching materials in the form of e-modules was carried out which will be developed for the web-based distance training learning process as an intermediary between trainers, students and teachers. The data analysis technique uses a feasibility instrument based on the national higher education standard (BSNPT). Modules circulating in the educational and religious areas of Medan are categorized as valid, meaning that innovation is needed.